The importance of tipping points for sustainable development - Lucas Bretschger; Matthias Leuthard (ETH Zurich, CER-ETH - Center of Economic Research, 2024)
Solving major sustainability problems such as climate change and the loss of biodiversity requires overcoming a fundamental dilemma: on the one hand, central decisions on the realignment of the economy and society should be quick and far-reaching, on the other hand, actual decision-makers are strongly oriented towards established structures, which entail great inertia and path dependencies. As a result, expectations and reality are often still far apart in sustainability policy. Tipping processes can play a decisive role in closing this gap and generally describe a non-linear and self-sustaining dynamic which can be triggered when a critical threshold (a tipping point) is crossed. The targeted promotion of crossing important thresholds can thus become a successful strategy for sustainability policy. In this paper, we highlight the importance and limitations of tipping dynamics in promoting sustainability. We develop an integrative formal approach to illustrate the characteristics of tipping dynamics in nature, technology, politics, society and the economy, and deepen the discussion using two case studies from economic history. Finally, we discuss implications for research, policy and institutions.
Keywords: Q54; Q55; Q56; O35; 330; Tipping point; sustainability; climate policies; non-linear development